PERAN BRAND TRUST MEMEDIASI PENGARUH ELECTRONIC WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN - Noviandini, Ni Putu Tissa; Yasa, Ni Nyoman Kerti (E-Jurnal Manajemen; Vol 10 No 11 (2021), 2021)
The purpose of this study is to examine and explain the effect of e-WOM on purchasing intention, the effect of purchase intention on brand trust, the effect of brand trust on purchasing intention, and to explain the role of brand trust in mediating e-WOM on purchasing intention. This study is based on Denpasar, especially Traveloka consumers. Probability sampling is used with 120 respondents. The data was collected using an online questionnaire, analyzed using path analysis and sobel test. The results showed that 1) e-WOM has a positive and significant effect on purchasing intention, e-WOM has a positive and significant effect on brand trust, brand trust has  positive and significant effect on purchasing intention, brand trust is significantly able to mediate the effect of e-WOM on purchasing intention. Based on the research results, it is hoped that Traveloka management can improve the management of product review features and discussion features to connect consumers, provide information in accordance with the reality in the field and can encourage consumers to make transactions at Traveloka. Keywords: e-WOM, brand trust, purchase intention